Association between serum IgM and all-cause mortality risk in Chinese centenarians: a prospective cohort study - Weiguang Zhang; Yuting Duan; Zhe Li; Yue Niu; Bin Wang; Zhe Feng; Ding Sun; Hao Li; Zehao Zhang; Zeyu Qu; Miao Liu; Hongyan Hu; et al. (Immunity & Ageing)
Abstract Background We investigated the associations between IgM, IgG, IgA, and IgE levels and all-cause mortality risk in Chinese centenarians. Methods All participants were from the China Hainan Centenarian Cohort Study. Eligible participants were divided into quartiles based on their IgM, IgG, IgA, and IgE levels. We used restricted cubic spline analyses, Cox regression analyses, and Kaplan–Meier survival curves to analyze associations between IgM, IgG, IgA, and IgE and all-cause mortality risk. Results A total of 906 centenarian participants were included in this study (81.2% female; median age, 102 years). During a median follow-up of 30.1 months, 838 (92.5%) participants died. Restricted cubic spline analysis revealed a nonlinear relationship (“L” type) between serum IgM level and all-cause mortality. Compared with the higher three quartiles of serum IgM level, the lowest quartile was associated with a higher risk of death (Q1 versus Q2-Q4: HR, 1.365; 95% CI, 1.166–1.598; P < 0.001). Among individuals for whom IgM < 0.708 g/L (Q1), the risk of all-cause mortality was 36.5% higher. Kaplan–Meier analyses showed that centenarians with lower serum IgM levels had significantly shorter median survival time (Q1 versus Q2-Q4: 26 months versus 32 months, log-rank P = 0.001). Conclusion Serum IgM levels in centenarians significantly correlated with the risk of death, suggesting that they are suitable for predicting the overall risk of death in centenarians and can be used as an independent predictor of death.